Pemikiran Al-Ghazali tentang Bahasa dan Pendidikan: Analisis Konseptual bagi Pengembangan Kurikulum Bahasa Arab Kementrian Agama di Sekolah Dasar: Implikasi Filosofis Pemikiran Al-Ghazali terhadap Tujuan dan Materi Bahasa Arab Kemenag - Ibnu Ansori; Kamal Yusuf (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The thought of Abu Ḥamid Al Ghazali (1058–1111 CE) holds a profound influence on Islamic educational theory, particularly in the relationship between language, ethics, and character formation. This study aims to conceptually analyze the relevance of Al Ghazali’s ideas on language and education in the context of developing the Arabic Language curriculum implemented by the ministry of religious affairs (Kemenag) at the elementary school level. The method employed in this study is a qualitative approach based on library research, utilizing content analysis of Al Ghazali’s seminal works such as Iḥya’ ‘Ulum Al-din, Mizan Al ‘amal, and Al Mustashfa Min ‘ilm Al Uṣul, as well as official documents of the Arabic Language Curriculum issued by the ministry of religious affairs (Kemenag) in 2013 and its revision in 2020. The results of the analysis indicate that Al Ghazali positions language as both a spiritual and epistemological instrument for understanding divine revelation, instilling values of adab (proper conduct), and shaping the moral character of learners. According to him, language is not merely a tool of communication but also a means of moral cultivation and the purification of intention within the educational process. This line of thought aligns with the direction of the ministry of religious affairs’ curriculum, which emphasizes the development of communicative competence, Islamic values, and religious character. However, the study reveals a gap between Al Ghazali’s philosophical ideals and the practical implementation of the curriculum in the field, where Arabic language instruction at the elementary level remains primarily focused on linguistic competence, with limited attention to its ethical and spiritual dimensions. This study concludes that the development of the Arabic Language curriculum at the elementary school level should integrate the three main pillars of Al-Ghazali’s thought tawḥid (the oneness of God), adab (proper conduct), and ḥikmah (wisdom) into every aspect of learning, including objectives, content, methods, and assessment. In doing so, the curriculum would not only produce students who are proficient in the Arabic language but also individuals of noble character who possess spiritual awareness in their use of language.